The mechanical mind in history - Husbands, Phil; Holland, Owen; Wheeler, Michael, 1960- (MIT, 2008)
The idea of intelligent machines has become part of popular culture. Tracing the history of the actual science of machine intelligence reveals a rich network of cross-disciplinary contributions, and the origins of ideas now central to artifical intelligence, artificial life, cognitive science and neuroscience.
"A Bradford book."
Keywords: Artificial intelligence -- History.; Artificial intelligence -- Philosophy.; elektronické knihy; electronic books